1993
DOI: 10.1111/j.1472-8206.1993.tb00253.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and electrophysiological properties of SR 57746A, a new, potent 5‐HT1A receptor agonist

Abstract: SR 57746A (1-[2-(naphth-2-yl) ethyl]-4-(3-trifluoromethylphenyl)-1, 2, 5, 6 tetra-hydropyridine hydrochloride) binds competitively, and with high affinity (Ki = 2.0 +/- 0.7 nM) to 5-HT1A receptors from rat hippocampus in vitro, but has much less affinity for other 5-HT receptor subtypes (IC50 > 650 nM). SR 57746A produces a concentration-dependent inhibition of forskolin-stimulated adenylate cyclase activity in rat hippocampal homogenates, with a maximal effect identical to that of 8-OH-DPAT, suggesting that S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…SR57746A has no a nity for the majority or neurotransmitter receptors except for the 5-HT 1A receptor for which this compound is a potent agonist (Bachy et al, 1993). As shown in the present study, the compound's e ects were not shared by 8-OH-DPAT, suggesting that the 5-HT 1A receptor is not involved in, or is not su cient by itself, to induce the neurotrophin-promoting e ect of SR57746A.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…SR57746A has no a nity for the majority or neurotransmitter receptors except for the 5-HT 1A receptor for which this compound is a potent agonist (Bachy et al, 1993). As shown in the present study, the compound's e ects were not shared by 8-OH-DPAT, suggesting that the 5-HT 1A receptor is not involved in, or is not su cient by itself, to induce the neurotrophin-promoting e ect of SR57746A.…”
Section: Discussionsupporting
confidence: 48%
“…In contrast, 6 h of IL-1 (10 U ml 71 ) incubation induced signi®cant increases of NGF mRNA (280% of control) and BDNF mRNA (206% of control; Table 1). While SR57746A has no or only very low a nity for the majority of neurotransmitter receptors, including bnoradrenergic receptors, whose stimulation can increase NGF production in cortical astrocytes (Schwartz & Mishler, 1990), the compound is a potent agonist for the 5HT 1A receptor (Bachy et al, 1993). The e ect of the 5HT 1A receptor agonist 8-OH-DPAT was therefore evaluated on neurotrophin mRNA levels in astrocyte cultures.…”
Section: E Ect Of Sr57746a On Neurotrophin Mrna Levelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Screening studies have shown that Xaliproden has high affinity for 5-hydroxytryptaminergic 5-HT1i\receptors (4,8,9). These receptors are coupled, via specific G /G o proteins, to inhibitory pathways (inhibition of adenyl cyclase (AC) activity and regulation of ion channels), and also stimulate phospholipase C (PLC) and the mitogen-activated protein kinase (MAPK) (10).…”
mentioning
confidence: 99%